Correlation between the structural characteristics, oxygen storage capacities and catalytic activities of dual-phase Zn-modified ceria nanocrystals1. Issue 7 (22nd July 2015) - Lin, Fangjian; Delmelle, Renaud; Vinodkumar, Thallada; Reddy, Benjaram M.; Wokaun, Alexander; Alxneit, Ivo
<x xml:space="preserve">Abstract</x> An excellent correlation between the structural properties and OSCs of dual-phase Zn-modified ceria nanocrystals is established. The detrimental effect of the secondary X-ray amorphous ZnO phase on soot oxidation is elucidated.